Bioeconomic Approach and Sustainable Management Innovation of Red Snapper (Lutjanus sp.) Resources at Coastal Fishing Port, Tegalsari - Simanjuntak, Susi Watina; Kusnandar, Kusnandar; Mulyani, Sri; Nugroho, Beni Sabdo; Alamsyah, Heru Kurniawan; Zuhry, Noor (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
Tegal City has considerable capture fisheries potential. One of the leading commodities in this area is Red Snapper (Lutjanus sp.), which has a high market demand in Indonesia. On the other hand, the waters off the North coast of Java in general have experienced overfishing and resource degradation. In connection with the above, it is necessary to conduct a comprehensive study involving biological and economic aspects in resource management. This study aims to analyze the bioeconomic aspects of Red Snapper fisheries as well as sustainable management innovations in PPP Tegalsari. This study uses a quantitativ approach, with descriptive-quantitative analysis. The purposive sampling method was carried out for sample determination, while data analysis used CPUE and Bioeconomics analysis. The results of the study show that the utilization of Red Snapper resources at Tegalsari Port produces maximum economic rent (π) and is ecologically safe in the condition of MEY balance compared to the condition of MSY and OAE, which is Rp 14.36 billion. The utilization rate of Red Snapper (Lutjanus sp.) has been in a fully exploited and over-exploited condition. The Red Snapper Effort Level has exceeded the limit of sustainable efforts (f > 100%). This condition is classified as critical because if the catch (effort) is not controlled, it can reduce fishermen's income and cause degradation of fishery resources. Therefore, mitigation efforts are needed by controlling arrest efforts and implementing stricter arrest quotas. The implications of this study are very closely related to the Measured Fishing (PIT) policy where fishing is controlled, proportional, fish resources and the environment are sustainable, as well as equitable economic growth.